(untitled) - Sarkan, Branislav; Holesa, Lukas (Doprava a spoje, 2012)
Driving cycles serve for the comparison of energetic performance of motor vehicles and measurement of production of emissions. The course of speeds and load of motor vehicle drive in a certain time interval is determined by means of said cycles. The contribution deals with individual driving cycles used in the world and serving for aforesaid actions.